Asuhan Keperawatan Jiwa Gangguan Persepsi Sensori Halusinasi Pendengaran Dengan Diagnosa Medis Skizofrenia Tak Terinci Di Rumah Sakit Jiwa Daerah Dokter Arif Zainudin Surakarta - Divana Indra; Cipto Cipto; Siswoko Siswoko; Kuswanto Kuswanto (Jurnal Studi Keperawatan, 2023)
Background: Mental health is when a person feels healthy and happy, is able to face life's challenges and accept others as he wishes, and has a positive attitude towards himself and towards others. So it requires a more serious handling. One of the mental disorders is schizophrenia. In clients with mental disorders, one of the symptoms that is often found is hallucinations. Hallucinations are synonymous with schizophrenia. All clients with schizophrenia experience hallucinations.Method : The method used in this case study is a narrative method which includes the implementation of nursing care for both patients with auditory hallucinations, the analysis is continued with discussion and results to get an overview between theory and practice of nursing care for both respondents.Results: After nursing actions were carried out for four meetings which were carried out to two respondents to control the hallucinations experienced by patients. At client evaluation Mr. E Mr. M strategies one through four can be carried out with an evaluation the client can re-do strategies one through four.Conclusion: Patients who experience auditory hallucination sensory perception disorders can be given nursing care by implementing strategies 1 to 4 as well as family support to support the patient's recovery.Keywords : mental disorders, audiotory hallucinations, nursing care